Optimization of recompression S-CO2 power cycle with reheating - Sarkar J.; Bhattacharyya S. (My University, 2025)
In the present study, optimization of compressor pressure ratio and intermediate pressure between HP and LP turbines leading to maximum thermal efficiency is implemented for a supercritical CO2 recompression cycle with reheating applicable to next generation nuclear reactors. Effects of various operating conditions and component performances on the optimal values and cycle efficiency are studied as well. Finally, a comparison between supercritical CO2 recompression cycles with and without reheating is presented. The optimization of recompression mass fraction shows that the present cycle configuration yields maximum thermal efficiency for nearly equal heat capacity values of both fluids in LTR. The effect of maximum cycle temperature on the optimum pressure ratio is negligible for lower values of minimum cycle temperature and maximum pressure, and the effect becomes significant with an increase in these parameters. Results show that the thermal efficiency improves with a decrease in minimum cycle temperature and with increase in maximum cycle temperature and pressure. The optimum intermediate pressure is exhibited to be higher than the geometric mean value between minimum and maximum pressure and a simple empirical correlation useful for optimum design is presented. The maximum efficiency improvement using reheating is calculated as 3.5% at optimum conditions. © 2009 Elsevier Ltd. All rights reserved.